Description and ontogeny of a 40-million-year-old parasitic isopodan crustacean: Parvucymoides dvorakorum gen. et sp. nov - Van der Wal, Serita; Schädel, Mario; Ekrt, Boris; Haug, Joachim T (PeerJ, 2021)
A collection of exceptionally well-preserved fossil specimens of crustaceans, clearly representatives of Isopoda, is presented here. Excavated from the late Eocene (approximately 40 million years ago) freshwater sediments of the Trupelník hill field site near Kučlín, Czech Republic, these specimens are preserved with many details of the appendages. The morphological characteristics of the fossils were documented using macro-photography with polarised light, as well as stereo imaging. These characteristics, especially including the trunk appendage morphology, were compared to those of related extant groups from different ontogenetic stages. All specimens are conspecific, representing a single species Parvucymoides dvorakorum gen. et sp. nov. Morphometric analysis of body shapes and sizes of the reconstructed fossils and related extant species were performed. These analyses provided insight into the ontogenetic stages of each reconstructed fossil specimen. In combination with the morphological assessment, the results indicate that the fossils represent at least two (possibly three) developmental stages, including immatures. The morphology of the appendages suggests that these fossils were parasites. The fossils are interpreted as either representatives of Cymothoidae or at least closely related to this group.
Keywords: Eocene; Cymothoida; Kučlín; fossil Cymothoidae; fish parasite